The concept of water law in the Polish legal system - Rakoczy, Bartosz (Polish Yearbook of Environmental Law, 2016)
“Water law” has become a standard term in both Polish language of the law and Polish legal language. It is used by both the legislator alone as well as in case law and legal doctrine[1]. However, the term is not used and interpreted unambiguously, which makes it difficult to determine the context in which the term was used and what it means at the specific time. It significantly determines the analysis of the concept of water law itself, whereas the scope of the analysis depends on the understanding of the term “water law”. [1] K. Szuma, Prawo wodne w systemie prawa ochrony środowiska, part 1 - Prawo i Środowisko 2011, No 1, p. 70-79, part 2 – Prawo i Środowisko 2011, No 2, p. 68-83.